Reforming Prank Content as a Media for Da'wah on Youtube Channels - Warliah, Wiwin; Putri, Ismatul Aini (JURNAL ISLAM NUSANTARA, 2022)
The prank phenomenon has mushroomed in modern society, especially in a cyber society. Prank content is a joke, joke, or comedy activity for both personal and communal, which has become a trend among Indonesian people, especially since 2019. Prank content as a communication message aims to provide entertainment (entertainment) to other people or (communicant). Even for contemporary preachers, prank content is used as 'reform' for da'wah media, for example, on Gus Aldi's Youtube channel. The purpose of this study is to analyze how to reform the content of prank content as a medium of propaganda on Gus Aldi's Youtube channel. The researcher uses a virtual ethnography method with the Cyber Media Analysis (AMS) technique which consists of the media room level, media documents, media objects, and experiences. The results of the study concluded that; 1) the content of prank content on Gus Aldi's Youtube channel represents the productivity and creativity of preachers in cyberspace; 2) the selection of Youtube media as a stimulus for the object of da'wah (message recipients); 3) determining the material for da'wah (Shalawat Nabi) to be a 'reinforcement' in the spiritual fulfillment and religiosity of cyber society.